Claiming Public Health Crisis to Regulate Sexual Outlets: A Critique of the State of Utah's Declaration on Pornography. - McKay, Kimberley; Poulin, Christopher; Muñoz-Laboy, Miguel (Archives of Sexual Behavior, 2021)
The article discusses the potential cultural and psychosocial impacts of the 2016 decision by government of Utah to declare pornography as a public health crisis. Topics include background on the governmental involvement in the management of sexuality through public health, the declaration by Utah's Governor Gary Herbert of pornography as a public health crisis, and criticism against using the public health crisis claim to regulate pornography usage.